2016
DOI: 10.1111/jse.12219
|View full text |Cite
|
Sign up to set email alerts
|

Tree of life for the genera of Chinese vascular plants

Abstract: We reconstructed a phylogenetic tree of Chinese vascular plants (Tracheophyta) using sequences of the chloroplast genes atpB, matK, ndhF, and rbcL and mitochondrial matR. We produced a matrix comprising 6098 species and including 13 695 DNA sequences, of which 1803 were newly generated. Our taxonomic sampling spanned 3114 genera representing 323 families of Chinese vascular plants, covering more than 93% of all genera known from China. The comprehensive large phylogeny supports most relationships among and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 98 publications
12
84
0
Order By: Relevance
“…The phylogeny based on complete chloroplast genomes using BI and ML methods found that the Apiales are sister to the Dipsacales (Fig. 3A), which agrees with recent phylogenies for this subclass based on other markers (Beaulieu, Tank & Donoghue, 2013; Wikström et al, 2015; Chen et al, 2016; The Angiosperm Phylogeny Group, 2016). However, using the MP method with the same data resulted in a phylogeny with the Asterales sister to the Dipsacales (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…The phylogeny based on complete chloroplast genomes using BI and ML methods found that the Apiales are sister to the Dipsacales (Fig. 3A), which agrees with recent phylogenies for this subclass based on other markers (Beaulieu, Tank & Donoghue, 2013; Wikström et al, 2015; Chen et al, 2016; The Angiosperm Phylogeny Group, 2016). However, using the MP method with the same data resulted in a phylogeny with the Asterales sister to the Dipsacales (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…We combined 328 newly generated sequences (Table S1) with sequences retrieved from GenBank (released December, 2012). The 328 newly generated sequences will be submitted to GenBank together with sequences newly generated in Chen et al () as an integrated contribution of the China Phylogeny Consortium (Chen et al, ). Voucher information for these new sequences and the methods of DNA extraction, gene amplification, and sequencing, as well as primer sequences, are reported in Chen et al ().…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the effect of evolutionary age of local floras on the biogeographical pattern of sexual systems (i.e., the per-grid proportions of the three sexual systems), we extracted the genus age from the phylogenetic tree of Chinese vascular plants constructed by Chen et al (2016) and calculated the average genus age for each grid cell. Moreover, we also evaluated the relationships between the proportions of sexual systems per grid cell and the phylogenetic diversity of local floras.…”
Section: Genus Age and Phylogenetic Diversitymentioning
confidence: 99%